1467. Association between Pathogen Load in the Upper Respiratory Tract and Severe Acute Respiratory Infections in Guatemalan Adults: Haemophilus influenzae, Staphylococcus aureus, Moraxella catarrhalis, Streptococcus pneumoniae, Klebsiella pneumoniae. (31st December 2020) - Hamid, Sarah; Milucky, Jennifer; Shang, Nong; Wolff, Bernard; Van Beneden, Chris; Winchell, Jonas; López, María Reneé; Clasen, Thomas; McCracken, John P
Abstract: Background: The causal attribution of bacterial pathogens to severe acute respiratory infections (SARI) is challenging because many bacteria are frequently detected in the upper respiratory tract of asymptomatic persons. Quantification of pathogen load may help differentiate asymptomatic pathogen carriage from clinically significant infection. We aimed to determine whether real-time PCR (rt-PCR) cycle threshold (Ct) values, as a proxy for bacterial load, differ between adults with SARI and asymptomatic adults. Methods: Adults with SARI (acute onset of fever and cough, requiring hospitalization) were frequency matched to asymptomatic adults (enrolled from trauma and orthopedic inpatient wards) by age group, catchment area, and enrollment date at three surveillance sites in Guatemala. Nasopharyngeal and oropharyngeal specimens were collected from all participants and tested for pathogens using rt-PCR. Using the Wilcoxon rank sum test, we compared the distributions and median Ct values between ill and asymptomatic adults in whom Haemophilus influenzae, Staphylococcus aureus, Moraxella catarrhalis, Streptococcus pneumoniae, and Klebsiella pneumoniae were detected. Results: Between October 2013 and October 2015, 304 adults with SARI and 174 asymptomatic adults were enrolled (Table). M. catarrhalis, S. aureus, and S. pneumoniae were detected with similar frequency in both groups. H. influenzae and K. pneumoniae were detected more frequently in asymptomatic adults. We found the greatest difference in Ct value distributions between ill (median Ct=30.8) and asymptomatic adults (median Ct=35.6) with S. pneumoniae detections (p< 0.01) (Figure). Median Ct values of H. influenzae (29.3 vs 31.1, p=0.04) and M. catarrhalis (29.2 vs 31.5, p=0.05) were also lower among adults with SARI. Frequency of select bacterial pathogen detection among adults with SARI and among asymptomatic adults, Guatemala, 2013-2015 Distributions of Ct values among adults with SARI and asymptomatic adults in whom a given bacterial pathogen was detected Conclusion: Pathogen loads of S. pneumoniae, H. influenzae, and M. catarrhalis were higher among adults with SARI than among asymptomatic adults, suggesting that Ct values may provide insight into SARI etiology for some pathogens, despite the similar frequency of detection among both ill and asymptomatic adults. Future work will normalize Ct values to account for variation in testing and analysis and explore the use of Ct values to estimate population attributable fractions of respiratory infections. Disclosures: All Authors : No reported disclosures